ANALISIS DAN DESAIN SISTEM INFORMASI PENGARSIPAN SURAT MASUK DAN SURAT KELUAR PADA DINAS LINGKUNGAN HIDUP PROVINSI SUMATERA BARAT - Gusnayetti Gusnayetti (Ensiklopedia of Journal, 2022)
Abstract: The Environmental Service of West Sumatra Province is a government agency that provides services and organizes benefits in the environmental field. The activities of the Department of the Environment include: formulation of policies; policy implementation; implementation of evaluation and reporting; administrative implementation; fostering the UPT and the Environmental Service Functional Group. In a government agency, information exchange activities cannot be separated from correspondence activities. Letters are used by the Environmental Service as a means of communication in collaboration with other individuals or agencies. The letter filing system at the Environmental Service still uses paper media as the main archive so that it often experiences difficulties in finding data, errors in data writing, and data loss. The purpose of this study was to produce an information system for archiving incoming and outgoing letters at the Environmental Service of West Sumatra Province. This study uses the Waterfall method, where user needs are the main point in making the system. The results of this study are an information system that can facilitate the filing system of incoming and outgoing mail that is currently running at the Environmental Service of West Sumatra Province and minimizes the risks that will occur.Keywords:Analysis, Archiving, Design, Information Systems, Waterfall